Stability, Accuracy and Cost of NEB and String Methods (Communications in Computational Physics, 2007)
In this paper, the zero-temperature string method and the nudged elastic band method for computing the transition paths and transition rates betweenmetastable states are investigated. The stability, accuracy as well as computational costof the two methods are discussed. The results are verified by numerical experiments.